2020
DOI: 10.1186/s12964-020-00622-w
|View full text |Cite|
|
Sign up to set email alerts
|

Loss of PTEN expression is associated with PI3K pathway-dependent metabolic reprogramming in hepatocellular carcinoma

Abstract: Background: Metabolic reprogramming, in which energetic metabolism changes from oxidative phosphorylation to glycolysis, is well-accepted as a hallmark of cancers including hepatocellular carcinoma (HCC). A growing body of evidence suggests the involvement of oncogenes and tumor suppressor genes in the control of metabolic reprogramming. In this study, we attempt to investigate whether loss of PTEN, a recognized tumor suppressor, drives metabolic reprogramming of HCC. Methods: Cancerous liver tissues were surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
2
21
0
Order By: Relevance
“…The addition of the metabolic modulators used in the second set of EFAs allowed us to calculate several metabolic parameters ( Supplementary Table S1 ) that have more informative value than the raw normalized measurements. They also allowed for a more accurate comparison between the two incubation conditions ( Marinangeli et al, 2018 ; Zhao et al, 2020 ). Metabolic parameters were calculated for each well as the average value of the measurements taken for that well in condition A minus the average value of the measurements taken for that well in condition B (see Supplementary Table S1 for a description of the conditions and Supplementary Figure S2 for a graphical representation).…”
Section: Methodsmentioning
confidence: 99%
“…The addition of the metabolic modulators used in the second set of EFAs allowed us to calculate several metabolic parameters ( Supplementary Table S1 ) that have more informative value than the raw normalized measurements. They also allowed for a more accurate comparison between the two incubation conditions ( Marinangeli et al, 2018 ; Zhao et al, 2020 ). Metabolic parameters were calculated for each well as the average value of the measurements taken for that well in condition A minus the average value of the measurements taken for that well in condition B (see Supplementary Table S1 for a description of the conditions and Supplementary Figure S2 for a graphical representation).…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, Stiles et al reported that hepatic Pten deletion in mice induced an increased glycogen synthesis in the liver [ 104 ]. In vitro, PTEN deficiency in human HCC cell lines (HepG2 and Huh7) is further associated with an increased glucose consumption [ 105 ], whereas its overexpression decreased glucose uptake by the HHCC cells [ 106 ]. Taken together, these previous studies clearly indicate that PTEN knockdown or knockout in hepatocytes triggers an increased glucose utilization.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the metabolic modulators used in the second set of EFAs allowed us to calculate several metabolic parameters (Table S1) that have more informative value than the raw normalized measurements. They also allowed for a more accurate comparison between the two incubation conditions [74,75]. Metabolic parameters were calculated for each well as the average value of the measurements taken for that well in condition A minus the average value of the measurements taken for that well in condition B (see Table S1 for a description of the conditions and Fig.…”
Section: Methodsmentioning
confidence: 99%